Synthesis, Crystal Structure, and DFT Calculations, of N1,N1 -diethyl-N4 -[(quinolin-2-yl)methylidene]benzene-1,4- diamine - Jamal , Asif; Faizi , Md. Serajul Haque; Haque , Navedul (Progress in Chemical Science Research Vol. 6, 2023)
The title compound N1, N1 -diethyl-N4 -(quinolin-2-ylmethylene)benzene-1,4-diamine (DQMBD) was synthesized by the condensation of the N1, N1 -diethyl-p-phenylenediamine and 2-quinolinecarboxaldehyde. The dihedral angle between the planes of the quinoline and phenylenediamine rings in the DQMBD is 178.9(3). In the crystal, molecules are connected by C—H \(π\) interactions, resulting in a chain that extends in the direction of the a-axis. The title compound was optimized by density functional theory (DFT) at the B3LYP/6-311++G (d,p) energy level and compared with the experimental data. The LUMO- HOMO energy gap is found to be 3.3080 eV.